БЕЗПЕРЕРВНИЙ ПРОФЕСІЙНИЙ РОЗВИТОК – СТАВЛЕННЯ ЛІКАРІВ - В. Л. Михайленко; А. І. Літвак (Проблеми екології та медицини)
Relevance. Staff development is an essential task of any organization, both large and small. Nowadays, professional knowledge is changing very rapidly, which requires persistent replenishment and acquisition of new skills throughout the professional career. In accordance with government documents (resolution of the Cabinet of Ministers of Ukraine as of March 28, 2018 № 302 and order of the Ministry of Public Health of Ukraine as of February 22, 2019 № 446), which changed the rules of professional retraining of doctors and their certification, wider introduction of modern forms of continuing medical education are encouraged. No research on the latest innovations has been conducted yet, which determines the timeliness of the present study. The aim of the study was to find out the opinion of doctors in a large city about the state's innovations regarding continuous professional development (CPD) and staff certification. Materials and methods. The study was conducted through the anonymous on-line survey (Computer Assisted Web Interviewing) of doctors in Odesa using the original questionnaire. The number of respondents were 653 (public medical facilities of Odesa). The sample structure was congruent by age, sex, medical specialties, etc. Results. Most doctors (over 70%) approve of changes in CPD. The main motives for CPD of doctors are striving for self-development (81.7%), the desire to acquire new knowledge (88.2%) as well as expand professional opportunities (66.1%). Doctors demonstrated their attitude as active and independent specialists, they prefer scientific and educational activities conducted in the places where they live (62.6%), as well as distance learning (45.8%), cycles of thematic improvement (62.1%). Primary care physicians have manifested greater activity in CPD issues. The financial component is an acute issue. Conclusions. For the successful continuation of innovations in CPD system in Ukraine, a comprehensive program of support for physicians is needed. The main partners in this should be the Ministry of Public Health of Ukraine, local governments, medical associations and societies, as well as a responsible business structure.